Experimental investigation of the effects of physical and geometric parameters of elongated strikers on penetration of barriers - Zakharov, V. M. (Journal of engineering physics and thermophysics)
Experimental investigations have been conducted into the penetration of elongated strikers into massive steel barriers of low and high hardness in a broad range of variation in the initial impact conditions. It has been established that at an elongated striker's velocity of impact against the barrier of 800-1200 m/s, its penetration into the barrier is complicated by the effects of barrier destruction asymmetry and loss of striker stability. The experiments have shown that in the investigated velocity range of the striker's interaction with the barrier, the said effects have substantial influence on the striker's penetration into the barrier.